Evaluation of a health care program for retirees in Ceará - Cruz, Telma Efigênia Tenório; Fraga, Maria de Nazaré de Oliveira (Rev Rene, 2012)
The fast ageing of the world´s population has brought up the need for public policies for the elderly and also to prepare them to enter into the condition of retirees. Research objectives: to know the profile of beneficiaries and their evaluation on the Integrated Action Program for Retirees in Ceará. Data collection happened from August 2009 to January 2010, through the application of questionnaires involving 90 elderly people. Most individuals were female, widowed, single or separated and with distinct profile concerning the majority of Brazilian workers and retirees. They evaluated positively the program and made a few suggestions. We concluded that the program is a public policy that, besides its several weaknesses, has been suffering from budget oscillations and containment due to changes of rulers and managers.